Evaluation of the position of the mental foramen in panoramic radiographs in a radiological center, Lima 2022 - Salas García, Nuria Lizbeth (2023)
Objectives: To determine the position of the mental foramen evaluated in panoramic radiographs in a radiological center, Lima 2022. Materials and Methods: A descriptive, cross-sectional and retrospective investigation was carried out; which consisted of a sample of 276 digital panoramic radiographs. The position of the mental foramen was evaluated using the observation technique, using the All Jasser classification for the horizontal dimension, as well as the Parmani classification for the vertical dimension; In addition, the analysis was carried out by descriptive statistics to measure the frequencies and percentage. Results: It was observed that the most prevalent mental foramen position was between the lower premolars in the horizontal dimension with 49.3% on the right side and 52.9% on the left side and in the vertical dimension the position of the mental foramen more The prevalence was between the apex of the first and second premolars with 49.3% on the right side and 52.9% on the left side. Conclusions: The most prevalent position of the mental foramen was between the lower first and second premolars.